2020
DOI: 10.1002/ase.2015
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Student Performance and Perceptions through a Flipped Anatomy Classroom: Shifting from Passive Traditional to Active Blended Learning

Abstract: One of the major challenges facing anatomy educators is delivering the anatomy materials in fewer hours with a reduction of anatomy courses in the integrated curricula. The flipped classroom modality may be an innovative solution. However, its effectiveness remains under debate due to a lack of outcome-based research and the mixed results of students' performance. The present study aimed to determine the outcome of the flipped classroom based upon the level of student cognition. The study investigated performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 113 publications
5
65
0
5
Order By: Relevance
“…The flipped classroom approach inverts traditional didactic design by having students engage in self‐directed learning activities with curated course resources at home before attending synchronous sessions with their instructor and peers (Lage et al, 2000 ). This approach lends itself well to remote teaching contexts, as the provision of asynchronous learning activities allows the students the flexibility to schedule their learning around other personal and academic activities (Fleagle et al, 2018 ; El Sadik & Al Abdulmonem, 2021 ). Studies on the flipped classroom in human anatomy have shown that it is associated with improved performance (Viveka et al, 2017 ; Chutinan et al, 2018 ), namely related to high‐order outcomes and knowledge retention (Morton & Colbert‐Getz, 2017 ; Day, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The flipped classroom approach inverts traditional didactic design by having students engage in self‐directed learning activities with curated course resources at home before attending synchronous sessions with their instructor and peers (Lage et al, 2000 ). This approach lends itself well to remote teaching contexts, as the provision of asynchronous learning activities allows the students the flexibility to schedule their learning around other personal and academic activities (Fleagle et al, 2018 ; El Sadik & Al Abdulmonem, 2021 ). Studies on the flipped classroom in human anatomy have shown that it is associated with improved performance (Viveka et al, 2017 ; Chutinan et al, 2018 ), namely related to high‐order outcomes and knowledge retention (Morton & Colbert‐Getz, 2017 ; Day, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While it is understandable that traditional classroom curricula are not designed to be implemented online (Harden and Hart, 2002; Payne, 2011; Green and Whitburn, 2016) especially during a pandemic, an adaptive blended learning approach may provide digitalized virtual or live interactions that can effectively replace the face‐to‐face option to implement a medical neuroscience course (Sandrone and Schneider, 2020). This is partly due to the fact that medical students benefit from adaptability in the use of digital learning platforms (Pereira et al, 2007; Winston et al, 2010; Ramklass, 2014; El Sadik and Al Abdulmonem, 2021) that are available in an integrated medical curriculum. This provides a unique opportunity to develop an adaptive blended learning pedagogy for the implementation during times that require that students be distanced from one another, such as during the Covid‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies actually demonstrates the positive attitude of medical students of developed or under developed countries towards online learning [10][11][12]. Anatomists have therefore been challenged to unbolt technology in attempt to attain best deliverables for their discipline, without the use of traditional teaching aids such as the cadaver, osteological specimens, prosected specimens, models, and microscopic slides and shifted the methods to electronic based [13,14]. At present, the virtual classroom is the only option for the anatomist, thereby omitting vital aspects of the hidden curriculum such as ethical-reasoning, empathy, respect, professionalism, interpersonal, and communication skills [15].…”
Section: Resultsmentioning
confidence: 99%